PENGEMBANGAN INSTRUMEN TINGKAT KETERLAKSANAAN PENILAIAN OTENTIK PADA PEMBELAJARAN FISIKA BERBASIS KURIKULUM 2013 DI KELAS X SMA NEGERI SE-KOTA PEKANBARU - Ali, Riri Hardiyanti; ', Zuhelmi; ', M Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the Vailidity of the Authentic Curriculum Based Curriculum 2013 in the eyes of the High School Physics subjects that are developed to support the level of implementation of Authentic School Assessment that includes attitude, knowledge, skills and authentic assessment. The type of research used is R & D (Research and Development). Development of Authentic assessment instruments includes preliminary studies, instrument planning, instrument development, instrument validation, and end products. The authentic assessment instrument developed in this research is a questionnaire that contains closed questions or open questions. From the results of the large index validation for attitude assessment 3.15, knowledge assessment 3.27, skill assessment 3.10, and authentic assessment step 3.4. Overall, the validation index of 3.21 categories is obtained. Thus it can be concluded that the authentic assessment instruments of high school students for physics subjects that have been developed are valid or fit to be used in analyzing the level of implementation of Authentic assessment of schools in applying attitude, knowledge, skills based on curriculum 2013.Keywords: Authentic assessment, Curriculum 2013, instrumen develompment